Predictors of SARS-CoV-2 Infection in Youth at a Large, Urban Healthcare Center in California, March–September 2020 - Newhouse, Caitlin N.; Saleh, Tawny; Fuller, Trevon; Kerin, Tara; Cambou, Mary C.; Swayze, Emma J.; Le, Catherine; Seo, Wonjae; Trejo, Marisol; Garner, Omai B.; Chandrasekaran, Sukantha; Nielsen-Saines, Karin (Frontiers in Pediatrics, 2021)
Objective: To understand which social, epidemiologic, and clinical risk factors are associated with SARS-CoV-2 infection in youth accessing care in a large, urban academic institution in southern California. Methods: We conducted a prospective cohort study with case-control analyses in youth who received testing for SARS-CoV-2 at our academic institution in Los Angeles during the first wave of the COVID-19 pandemic (March -September 2020). Results: A total of 27,976 SARS-CoV-2 assays among 11,922 youth aged 0-24 years were performed, including 475 youth with positive SARS-CoV-2 results. Positivity rate was higher among older, African American and Hispanic/Latinx youth. Cases were more likely to be from non-English speaking households and have safety-net insurance. Zip codes with higher proportion of Hispanic/Latinx and residents living under the poverty line were associated with increased SARS-CoV-2 cases. Youth were more likely to have positive results if tested for exposure (OR 21.5, 95% CI 14.6-32.1) or recent travel (OR 1.5, 95% CI 1.0, 2.3). Students were less likely to have positive results than essential worker youth (OR 0.5, 95% CI 0.3-0.8). Patterns of symptom presentation varied significantly by age group; number of symptoms correlated significantly with age in SARS-CoV-2 cases (r=0.030, p<0.001). SARS-CoV-2 viral load did not vary by symptom severity, but asymptomatic youth had lower median viral load than those with symptoms (21.5 vs 26.7, p = 0.009). Conclusions: Socioeconomic factors are important drivers of SARS-CoV-2 infection in youth. Presence of symptoms, exposure and travel can be used to drive testing in older youth. Policies for school reopening and infection prevention should be tailored differently for elementary schools and universities.